PENGEMBANGAN VARIASI LATIHAN KECEPATAN REAKSI PENJAGA GAWANG FUTSAL - Akhmad Taufiq; Rahma Dewi (Journal Physical Health Recreation (JPHR), 2021)
This study aims to develop a form of reaction speed training variation in the futsal game in 2021. The population in this study were all SKP Fc goalkeeper athletes, Amir Hamzah, and Bersama Fs. The form of the small group variation that has been made is validated by 3 experts, 1 futsal coach, 1 expert in sports, and 1 expert in language, where the percentage of validity is 58%-97% taken from the smallest to the largest percentage value of the overall results. The method used is the research and development (R&D) method. The form of the large group variation that has been made is validated by 3 experts, 1 futsal coach, 1 expert in sports, and 1 expert in language, where the percentage of validity is 86%-97% taken from the smallest to the largest percentage value of the overall results. The method used is the research and development (R&D) method. The results of the small group test involving 6 futsal goalkeeper athletes SKP Fc and Amir Hamzah showed that the 20 variations of the exercise had met the appropriate criteria. The percentage of validity of the questionnaire that has been distributed to the sample shows that 77%-96% is taken from the smallest to the largest percentage value of the overall results. The results of the large group test of 14 futsal goalkeeper athletes SKP Fc, Amir Hamzah, and Bersama Fs showed that the 20 variations of the exercise had met the criteria for use. The percentage of validity of the questionnaire that has been distributed to the sample shows that 84%-96% is taken from the smallest to the largest percentage value of the overall results. It can be concluded that the 20 models of exercise variations are good for increasing the ability and reaction speed of futsal goalkeepers and interesting exercises, because they are very important in training so that these exercises do not.